A Comparative Study of Green and Non-Green Environment on Mental Health and Emotional Maturity - Dipankar kumar (Dr. Chinmay Pandya, 2018)
Research  from a variety of scientific fields suggests that physical activity in nature and feelings of connection to nature enhance psychological health and well-beings. The main purpose of this research was to find out mental health and emotional maturity among green and non-green environment. The total sample consisted of 120 students out of which 60 green and 60 non-green environment were selected purposively, non-probability sampling technique, from Dev Sanskriti Vishwavidyalaya, Haridwar with age group of 20-24 years, average age group of 22 years. Ex post facto research design used in following study i.e. without previous intervention. Mental health was measured for the selected subjects using the questionnaire developed by Dr. (Smt) Kamlesh Sharma and Emotional Maturity Scale by Dr. Yashvir  Singh and Dr. Mahesh Bhargav. The obtained data was analyzed t-test to know the mean difference between green and non-green environment and Karl Pearson correlation method was used to know the relation between emotional maturity and mental health variables. Here t-test result revealed that there is a significant difference in emotional maturity and mental health at 0.05 level. t-test statistical method used as to examine the significance of hypothesis. Also a  positive correlation was observed between mental health and emotional maturity. As per above result it shows that green environment highly impacts our overall dimensions of life i.e. physical, mental, emotional as well as spiritual health.